2013
DOI: 10.1177/2158244013512133
|View full text |Cite
|
Sign up to set email alerts
|

Recovery From Comorbidity

Abstract: Comorbidity among mood, anxiety, and alcohol disorders is common and burdensome, affecting individuals, families, and public health. A systematic and integrative review of the literature across disciplines and research methodologies was performed. Supradisciplinary approaches were applied to the review and the ensuing critical appraisal. Definitions, measurement, and estimation are controversial and inconstant. Recovery from comorbidity cannot be easily extricated from a sociocultural milieu. Methodological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 156 publications
(334 reference statements)
0
10
0
2
Order By: Relevance
“…In support of this statement, our results show a trend towards a higher and more stable relationship between anxiety and cannabis use disorders that might eventually require treatment ( OR = 1.68, 95% CI : 1.23-2.31), than cannabis use alone ( OR = 1.24, 95% CI : 1.06-1.45; Table 4 ). Similarly, higher rates of comorbidity would be expected in vulnerable populations often not included in the population-based surveys due to being homeless, imprisoned, or inpatient in psychiatric or rehabilitation institutions [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this statement, our results show a trend towards a higher and more stable relationship between anxiety and cannabis use disorders that might eventually require treatment ( OR = 1.68, 95% CI : 1.23-2.31), than cannabis use alone ( OR = 1.24, 95% CI : 1.06-1.45; Table 4 ). Similarly, higher rates of comorbidity would be expected in vulnerable populations often not included in the population-based surveys due to being homeless, imprisoned, or inpatient in psychiatric or rehabilitation institutions [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, the findings described above are important because they demonstrate the overlap in the experiences of those living with a single disorder and those living with co-occurring disorder. The frequent overlap between serious mental illness and substance abuse suggests that a significant number of participants in previous recovery studies were likely living with a co-occurring disorder; however, recovery related specifically to co-occurring disorder has not been sufficiently investigated (Carter et al 2013). Additionally, our findings demonstrate significant overlap in consumer and staff definitions of recovery, which, as far as the authors are aware, has not been demonstrated within a single study.…”
Section: Discussionmentioning
confidence: 99%
“…Those with co-occurring disorder are at higher risk for a number of negative outcomes (e.g., poor treatment response, homelessness, incarceration, substance use relapse, re-hospitalization) than those with a single disorder (Abram and Teplin 1991; Carter et al 2013; Caton et al 2005; Drake et al 1989; Susser et al 1991). One reason proposed for these negative outcomes is a lack of understanding of recovery as it relates to co-occurring disorder, which is rooted in the separation between mental health and substance abuse treatment systems that ignores the complex realities of co-occurring disorder (Drake et al 2008; White et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It sets out to analyse how central participants in the treatment processclients and professionalsperceive the relevance of treatment-related factors for the recovery process. Research focusing on the person's own experience of both AOD and mental health problems is scarce (Carter, Fisher, and Isaac 2013;Cruce, Öjehagen, and Norström 2012;Ness, Borg, and Davidson 2014) but is stressed as important for gaining knowledge of factors that are important in their recovery process (Beredsford 2000;Davidson et al 2001).…”
Section: Introductionmentioning
confidence: 99%